(3eLehY aj GdcjejGAs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NGdbfG hUdi Gddg Ydi UahJg ef Ndbg eMeO hbO SejJg cJGH GdMGUd hPdc Cf SjOi LYaQ Hf eMeO UdhGJ Gddg Ydjg bGd di aeG GdMGUd GdCf HYO gPg GdcJH ai GdehGRjf s
(3BNQgG (B:s
(3Ef GdVQhQI gi GdHM hgj GdEfJbGe hgj GdSjGSI Je cJGH GdMGUd ai Yde GdejRGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs